Analysis of Labor Women At Star Hotels in the city of Pekanbaru - Monika Aliya Putri; Harlen '; Toti Indrawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in the city of Pekanbaru in 2013. This study aims to determine how the image of women in the labor-star hotel in the city of Pekanbaru is viewed from the aspect of education, past work, income, region of origin, and the factors driving women working in five-star hotel in the city Pekanbaru. This study uses primary data collected directly from the respondents on the female labor-star hotel in the city of Pekanbaru. The population in this study were all women in labor-star hotel in the city of Pekanbaru is classified at 3.4 and 5 star hotel that is numbered 511 people. While the sample used in this study amounted to 100 people. Secondary data were obtained from the Department of Culture and Tourism of Pekanbaru, Central Bureau of Statistics (BPS) of Pekanbaru. Engineering data was collected directly by visiting the employment of women in the five-star hotel in the city of Pekanbaru. This study analyzed using descriptive analysis method. Based on the survey results revealed that female employees who worked at the five-star hotel in the city of Pekanbaru seen from the aspect of education, which is dominated workforce education level diploma. Then views of the work, where workers who work at five-star hotel in the city of Pekanbaru has over 5 years experience. Viewed from the aspect of labor income, where the amount of earned income workers who worked at the hotel in Pekanbaru City Star above the minimum wage and depend on the position occupied. From the aspect of the origin, generally derived from the city of Pekanbaru. Then the drivers of women working in five-star hotel in the city of Pekanbaru is the salary offered as expected.Keywords: Woman, Labor, Hotel